2018
DOI: 10.4293/jsls.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Intestinal Pylorus-Sparing Surgery for Morbid Obesity

Abstract: Background and Objective:The Roux-en-Y duodenal switch (RYDS) is one of the most efficient forms of bariatric surgery. However, diarrhea, malnutrition, ulcers, and internal hernias have hampered its widespread adoption. The stomach intestinal pylorus-sparing (SIPS) procedure was developed to alleviate these sequelae while retaining the same weight loss as the RYDS. In this study, we report our midterm experience with this novel technique.Methods:Retrospective analysis was performed on data from 225 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…A los 12 meses, con un 62% de seguimiento, el %PEP promedio fue 72%, y no se reportaron complicaciones relacionadas con la anastomosis duodeno-ileal o mortalidad 15 . Recientemente Neichoy et al, describieron una serie con 225 pacientes a los cuales se le realizó SIPS 16 . El promedio de IMC preoperatorio fue 52,4 Kg/m 2 , y el %PEP a los 2 años de seguimiento fue 89%.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A los 12 meses, con un 62% de seguimiento, el %PEP promedio fue 72%, y no se reportaron complicaciones relacionadas con la anastomosis duodeno-ileal o mortalidad 15 . Recientemente Neichoy et al, describieron una serie con 225 pacientes a los cuales se le realizó SIPS 16 . El promedio de IMC preoperatorio fue 52,4 Kg/m 2 , y el %PEP a los 2 años de seguimiento fue 89%.…”
Section: Resultsunclassified
“…El promedio de IMC preoperatorio fue 52,4 Kg/m 2 , y el %PEP a los 2 años de seguimiento fue 89%. La remisión de DM fue 89%, y los autores reportaron solo 5 filtraciones (2,2%) de la anastomosis duodeno-ileal, y no reportaron síndrome de Dumping durante el seguimiento 16 . Cottam et al, realizaron un estudio comparativo entre SIPS versus BPD-DS 17 con 61 pacientes por rama de estudio.…”
Section: Resultsunclassified
“…Recently, there have been several reports on the outcomes of SADI-S procedure [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. One of the articles published by Neichoy et al [16] on the midterm outcomes of SADI-S reported EWL of 88% at 24 months. This was very similar to the weight loss reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinical knowledge, expert opinion, and published peer-reviewed scientific evidence, the International Federation for the Surgery of Obesity and Metabolic Disorders considered the SADI-S (and its variant [stomach intestinal pylorus-sparing surgery]) an established bariatric procedure [14]. In recent years, there have been few reports on the short-and mid-term outcomes of this procedure [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In terms of weight loss, the SADI-S and RYGB had statistically similar weight loss; however, the weight loss was statistically higher in patients undergoing SADI-S procedure than SG [21,30].…”
mentioning
confidence: 99%
“…Increasing common channel length to 300 cm reduces malabsorption significantly. 11,12 But, access to the biliary tract is lost in the SADI S procedure. Sleeve gastrectomy with loop gastroileal bypass (SG LGIB; Fig.…”
mentioning
confidence: 99%